Low physical activity work-related and other risk factors increased the risk of poor physical fitness in cement workers (Faculty of Medicine Universitas Indonesia, 2009)
Aim Low physical activity causes poor physical fitness, which leads to low productivity. The objective of this study was to determine the effects of low work-related physical activity and other risk factors on physical fitness. Methods This study was done in February 2008. Subjects were workers from 15 departments in PT Semen Padang, West Sumatera (Indonesia). Data on physical activities were collected using the questionnaire from the Student Field Work I Guidebook and Hypertension-Geriatric Integrated Program of the Faculty of Medicine, Universitas Indonesia 2003. Physical fitness was measured using the Harvard Step Test. Results A number of 937 male workers aged 18 - 56 years participated in this study. Poor physical fitness was found in 15.9% of the subjects. Low work-related physical activity, smoking, lack of exercise, hypertension, diabetes mellitus, and asthma were dominant risk factors related to poor physical fitness. Subjects with low compared to high work-related activity had a ten-fold risk of poor physical fitness [adjusted odds ratio (ORa) = 10.71; 95% confidence interval (CI) = 4.71-24.33]. In term of physical exercise, subjects who had no compared to those who had physical exercise had a six-fold risk of poor physical fitness (ORa = 6.30; 95%CI = 3.69-10.75). Conclusion Low work-related physical activities, smoking, lack of exercise, hypertension, diabetes mellitus, and asthma were correlated to poor physical fitness. It is, among others, therefore necessary to implement exercises for workers with poor physical fitness. (Med J Indones. 2009;18:201-5)